2009
DOI: 10.1007/s12640-009-9054-9
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Regulating proNGF Action: Multiple Targets for Therapeutic Intervention

Abstract: Neurotrophins are initially synthesized as precursor forms, that are cleaved to release C-terminal mature forms that bind to Trk receptors to initiate survival and differentiative responses. Recent studies suggest that the precursor form of NGF (proNGF) acts as a distinct ligand by binding to a receptor complex of p75 and sortilin to initiate cell death. Induction of proNGF and p75 have been observed in multiple pathological states and injury models in the central nervous system, and blockade of proNGF/p75 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Treatment of our diabetic animals with atorvastatin exerted similar protective effects to FeTPPs in reducing peroxynitrite and 4-HNE adducts, as well restoring the balance between NGF and proNGF to normal levels. Accumulation of proNGF after injury has been detected in several diseases of the central nervous system such as Alzheimer's, where pro-oxidative and pro-inflammatory milieus can reduce protease activity and NGF cleavage [8,9]. Of note, we believe that this is the first report showing clinical and experimental evidence of significant accumulation of proNGF in the diabetic eye.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Treatment of our diabetic animals with atorvastatin exerted similar protective effects to FeTPPs in reducing peroxynitrite and 4-HNE adducts, as well restoring the balance between NGF and proNGF to normal levels. Accumulation of proNGF after injury has been detected in several diseases of the central nervous system such as Alzheimer's, where pro-oxidative and pro-inflammatory milieus can reduce protease activity and NGF cleavage [8,9]. Of note, we believe that this is the first report showing clinical and experimental evidence of significant accumulation of proNGF in the diabetic eye.…”
Section: Discussionmentioning
confidence: 57%
“…Whether retinal microglial cells play a role in the initial proNGF secretion or sustain a regulatory loop of neurotrophin production during diabetic retinopathy remains to be explored. While proNGF is cleaved intracellularly by furin, with mature NGF being trafficked to secretory vesicles [9], it is cleaved extracellulary by MMP-7 [8]. Unlike most other family members of MMPs, MMP-7 is constitutively expressed by most adult tissue and its activity is redoxregulated [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings by our group showed that diabetes-induced peroxynitrite formation impairs cleavage and maturation of NGF, leading to accumulation of its precursor 'proNGF' at the expense of the mature NGF levels, both in experimental models and in clinical diabetes [10]. Accumulation of proNGF after injury has been detected in several neurodegenerative diseases, such as Alzheimer's, [11,12]. However the role of proNGF in the diabetic retina and the specific molecular mechanism regulating proNGF production and its subsequent effects on retinal neurodegeneration are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…ProNGF has been best characterized as a cytokine induced after neuronal injury in the central and peripheral nervous systems (Hempstead, 2009). Under these conditions, proNGF promotes neuronal apoptosis, and infusion of function-blocking antibodies specific for proNGF rescues most p75 NTR -expressing neurons after central neuron axotomy or seizures (Harrington et al, 2004;Volosin et al, 2006).…”
Section: P75 Ntr Deficiency Provides Protection From Infarct Expansionmentioning
confidence: 99%